Simulation of Ultrafast Optical Transitions using Genetic Algorithm - Dargys, A. (Nonlinear Analysis: Modelling and Control, 2001)
The purpose of this paper is to investigate the possibility of application of the genetic algorithm to quantum control of electronic transitions between energy bands in solids. In particular, the hole transitions between valence bands induced by ultrashort (femtosecond duration) electric field pulse will be considered. Examples are presented to illustrate the efficiency of the algorithm in this case.
Keywords: electronic transition; energy bands; genetic algorithm